Forging a scientific alliance to rebut claims on incompatibility of water management in CSA principles of rice production - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The outcome can be seen in a widely recognized mitigation potential of of water saving techniques in rice that has been put into question by recent PNAS article. This concerted response with renowned scientists in this field was crucial for corroborating the overall CSA concept that CCAFS has developed for rice production.